1996
DOI: 10.1055/s-2008-1052223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of new Titanium Cerebral Aneurysm Clips on MRI and CT Images

Abstract: We studied the effects of newly developed aneurysm clips made of a titanium alloy (manufactured by Aesculap, A.G.) on the quality of MR and CT images. Prior to clinical application in twenty patients, the effects of five types of conventional aneurysmal clips on MR images were examined utilizing a phantom. When compared with conventional aneurysm clips, the new titanium clips produce only limited artifacts and yielded improved images in patients who underwent aneurysm clipping post-operative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Previous reports investigating magnetic qualities of aneurysm clips indicated that aneurysm clips made from stainless steel alloy, Phynox, Elgiloy, commercially pure titanium, and titanium alloy were safe at 1.5 Tesla (1)(2)(3)5,8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, as previously discussed, few studies have been performed to evaluate magnetic field interactions for implants in association with MR systems operating above 1.5 Tesla.…”
Section: Aneurysm Clipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports investigating magnetic qualities of aneurysm clips indicated that aneurysm clips made from stainless steel alloy, Phynox, Elgiloy, commercially pure titanium, and titanium alloy were safe at 1.5 Tesla (1)(2)(3)5,8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, as previously discussed, few studies have been performed to evaluate magnetic field interactions for implants in association with MR systems operating above 1.5 Tesla.…”
Section: Aneurysm Clipsmentioning
confidence: 99%
“…These factors can greatly influence the MR safety aspects of these implants. While certain aneurysm clips are a contraindication for the MR environment, others classified as nonferromagnetic or weakly ferromagnetic are deemed safe for patients or individuals exposed to MR systems operating at 1.5 Tesla or less (1)(2)(3)(4)(5)8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Aneurysm Clipsmentioning
confidence: 99%
“…Since the introduction of titanium alloy clips, the occurrence of metallic artifacts adjacent to the clip has greatly decreased, resulting in widespread usage of titanium alloy clips. Although clips made from titanium alloy permit better visualization in the clip vicinity than those made from cobalt alloy 3 , 11 , 12 , 14 , 16) , the latter still play a large clinical role due to several advantages, including high tensile strength, high closing force, and extra-large and variously fenestrated clip profiles 8) . Therefore, we wanted to determine whether there were factors other than the clip property itself influencing the cobalt clip artifacts that could be easily managed.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature have demonstrated that titanium clips have significantly fewer artifacts on MRI and CT images (14). KATO et al (11) studied 20 patients with 26 aneurysms and demonstrated that titanium clips produce only limited artifacts and yield improved images in patients who undergo aneurysm clipping. WICHMANN et al ( 17) conducted a study on magnetic resonance characteristics of aneurysm clips made of titanium and found that the titanium aneurysm clips improved the image quality on MRI.…”
Section: Discussionmentioning
confidence: 99%